Un estudio de caso de la estrategia administrativa basada en comités - Enrique Vílchez-Quesada; Gaby Ulate-Solís; Ricardo Monge-Gapper (Universidad Nacional, Costa Rica, 2009)
The theory of curricular administration is applied in order to explain the use of the strategy of management committees in institutions of elementary and high school education. A case study is carried out in an educational institution of the metropolitan area; an institution known for organizational features that are common in a national reality that affects the malpractice of this strategy. It is established within the case study, some of causes of its abuse in the particular context of the educational institution "Unidad Pedagógica José Rafael Araya Rojas" located in the "Tibás, La Florida" community and in the light of these results, some recommendations are suggested in order to improve the use of the administrative strategy based on committees.